Acetylene as a Driving and Organizing Molecule in One‐Pot Transition‐Metal‐Free Synthesis of Furans using Chalcones and their Analogues. Issue 6 (24th April 2017) - Trofimov, Boris A.; Bidusenko, Ivan A.; Schmidt, Elena Yu.; Ushakov, Igor' A.; Vashchenko, Alexander V.
Abstract: Acetylene reacts with chalcones and their heterocyclic analogues in NaO t Bu/DMSO catalytic system (70 °C, 15 min) to afford substituted furans in a yield of up to 85 %, thus providing a simple and technologically feasible access to rare furan compounds. Abstract : Basic approach : A simple NaO t Bu/DMSO catalytic system is used for the synthesis of substituted furan compounds using acetylenes and chalcone derivatives. A yield of up to 85 % was obtained for the furan products.